2022
DOI: 10.3390/su14063640
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Adsorption Equilibrium in the Removal of Azo-Anionic Dyes by Modified Cellulose

Abstract: This study introduces a new and bio-friendly adsorbent based on natural and cetyltrimethylammonium chloride (CTAC)-modified adsorbent prepared from wheat straw residues for the removal of Congo red (CR) and tartrazine azo-anionic dyes from aqueous solution. The adsorbent was characterized by thermogravimetric analysis (TGA), calorimetric differential (DSC), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM/EDX), and pH point of zero charge (pHPZC) techniques. It was found that decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 56 publications
0
33
0
1
Order By: Relevance
“…Nevertheless, for longer contact times, a decrease in the removal of all metals was evidenced, as shown in Figure 5 . Other authors reported similar results for equilibrium times between adsorbent and adsorbate, which varied between 5 and 40 min, using solutions contaminated with different heavy metals and biosorbents of crambe [ 41 ], cashew-nut shell [ 56 ], cassava peel [ 57 ] and pinus bark [ 58 ]; likewise, it was observed that the adsorption kinetics is influenced by chemical modifications to the biomass [ 59 , 60 ], so the removal rates of biosorbents T2, T3 and T4 were higher than biosorbent T1.…”
Section: Resultsmentioning
confidence: 71%
“…Nevertheless, for longer contact times, a decrease in the removal of all metals was evidenced, as shown in Figure 5 . Other authors reported similar results for equilibrium times between adsorbent and adsorbate, which varied between 5 and 40 min, using solutions contaminated with different heavy metals and biosorbents of crambe [ 41 ], cashew-nut shell [ 56 ], cassava peel [ 57 ] and pinus bark [ 58 ]; likewise, it was observed that the adsorption kinetics is influenced by chemical modifications to the biomass [ 59 , 60 ], so the removal rates of biosorbents T2, T3 and T4 were higher than biosorbent T1.…”
Section: Resultsmentioning
confidence: 71%
“…From the parameters in Table 2 , it can be said that the Freundlich model best fits the experimental adsorption equilibrium data of As(III) on Ag@PDMAEMA-g-PET and PDMAEMA-g-PET TeMs, indicating that the adsorption process occurs in the form of multilayers with different adsorption energies and non-uniform heat distribution, due to the heterogeneity of the active centers of the adsorbents. The ions first occupied active adsorption sites that present strong interactions, thereby decreasing the interactions [ 93 ]. The value was higher when As(III) adsorption took place on Ag@PDMAEMA-g-PET, indicating a higher selectivity than DMAEMA-g-PET.…”
Section: Resultsmentioning
confidence: 99%
“…Equilibrium adsorption isotherm study is an important factor that optimizes the application of adsorbents by describing the interactions between the adsorbate and the adsorbent. The isotherm studies are carried out through the ratio of the absorbed quantity to the concentration of adsorption equilibrium or pressure at a constant temperature [18]. The isotherm studies evaluate the relationship between the amount and concentration of a substance removed from a liquid phase per unit mass of adsorbent at a constant temperature.…”
Section: Equilibrium Isotherm Modelingmentioning
confidence: 99%
“…The highest bleaching efficiency observed was 83.2% at 50 minutes using 3 g of AAMC. It was observed that increasing the dosage of activated clay to 7 g using the same quantity of crude palm oil reduced the equilibrium concentration in the medium thereby reducing the adsorption capacity [18]. [6] observed a decrease in the absorbance of the bleached oils following the increase in the adsorbent dosage of acid-activated Kangole clay by up to 4%.…”
Section: Effect Of Adsorbent Dosage On the Bleaching Efficiencymentioning
confidence: 99%
See 1 more Smart Citation